QIRA’AH, RIWAYAH, THARIQ DAN WAJH DALAM VARIASI BACAAN AL-QUR’AN (STUDI SAMPLE RIWAYAT HAFSH DARI IMAM ASHIM) - Salim, Muhammad Agus (El-Mu'Jam. Jurnal Kajian Al Qur'an dan Al-Hadis, 2022)
For those who want to study the science of qira'at, they must know the difference between four key terms. Some people sometimes find it difficult to differentiate and then just mix them up. The four terms are qira'ah, riwayah, thariq, and wajh. In the science of Qira'at, mixing thariq in reading the Qur'an is called talfiq, takhlith or tarkib. Scholars who are experts in qira'at have warned the qurra' not to do talfiq in reading the Qur'an. Therefore, it is important for the qura' to study the narration of Hasfh from Imam Ashim which is used as a reference by most Muslims, especially in Indonesia. This research is entirely library research taking data from literature that is related to the research theme. The analysis technique in this writing uses a content analysis model by exploring and analyzing the thoughts or views of Jama'ah Tabligh on the Hadiths of the Prophet that they practice in their daily lives.